CO2 Laser Cutting of Hot Stamping Boron Steel Sheets - Pasquale Russo Spena (Metals, 2017)
This study investigates the quality of CO2 laser cutting of hot stamping boron steel sheets that are employed in the fabrication of automotive body-in-white. For this purpose, experimental laser cutting tests were conducted on 1.2 mm sheets at varying levels of laser power, cutting speed, and oxygen pressure. The resulting quality of cut edges was evaluated in terms of perpendicularity tolerance, surface irregularity, kerf width, heat affected zone, and dross extension. Experimental tests were based on a L9(34) orthogonal array design, with the effects of the process parameters on the quality responses being determined by means of a statistical analysis of variance (ANOVA). Quadratic mathematical models were developed to determine the relationships between the cutting parameters and the quality responses. Finally, a routine based on an optimization criterion was employed to predict the optimal setting of cutting factors and its effect on the quality responses. A confirmation experiment was conducted to verify the appropriateness of the optimization routine. The results show that all of the examined process parameters have a key role in determining the cut quality of hot stamping boron steel sheets, with cutting speed and their interactions having the most influencing effects. Particularly, interactions can have an opposite behavior for different levels of the process parameters.